The use of dentin adhesive systems available for clinical dental practice (Research, Society and Development, 2023)
Objective: to present, through a literature review, updated knowledge about adhesive systems, application techniques and bonding mechanisms, thus offering clinicians better results when choosing excellent materials to meet their clinical needs. Materials and Methods: The selection of articles was carried out through an electronic search in the Scielo, PubMed and Lilacs databases. 55 articles published between 1992 and 2022 were considered eligible. Results and discussion: adhesive systems available on the market can be classified into three categories: conventional, self-etching and universal. The present study presents us with significant results with the diversity of these systems that the market presents, however, in addition to the material being of high quality, it must be associated with knowledge of the application technique and theoretical/practical knowledge so that the desired result is achieved. Conclusion: the available studies show us that the association of accurate technical knowledge is completely related to a successful result in the clinical application of adhesive systems.